A Proposed School for Traditional Building Arts & Crafts in Kalongo, Uganda - Matthew Espeland (Journal of Traditional Building, Architecture and Urbanism)
Uganda is headed for exponential growth both in its population and in its building stock. The buildings of small Ugandan market communities such as Kalongo, a remote village in the north, reflect two distinct construction systems, as contemporary building practices have turned their back on tradition. Interventions by foreign NGOs in the area have contributed to the stigmatization of local building traditions as representing underdevelopment. This proposed design project for a School for Traditional Building Arts & Crafts in Kalongo seeks to bridge the disconnect between building traditions and the growing requirement for durable, sustainable buildings. The proposal sets out the concept of an innovative way of building through the elevation of local materials and traditions on a new scale.